Perovskite-based proton conducting membranes for hydrogen separation: A review - Hashim, S.; Somalu, M.; Loh, K.; Liu, Shaomin; Zhou, W.; Sunarso, J. (Elsevier Ltd, 2018)
Hydrogen is considered a fuel of the future due to its diversified supply and zero greenhouse gas emission. The application of advanced membrane technology for hydrogen separation within the larger hydrogen production process context can substitute the use of more expensive and energy intensive cryogenic distillation and pressure swing adsorption technologies. This review overviews the basic aspects and progresses in perovskite-based proton conducting hydrogen separation membranes. Different configurations such as symmetric, asymmetric, hollow fiber, and surface modified perovskite membranes with various compositions are discussed and summarized. The challenges and future directions of such membranes are also elaborated.